Interpersonal Circumplex Profiles Of Persistent Depression: Goals, Self‐Efficacy, Problems, And Effects Of Group Therapy. Issue 6 (8th July 2016) - Locke, Kenneth D.; Sayegh, Liliane; Penberthy, J. Kim; Weber, Charlotte; Haentjens, Katherine; Turecki, Gustavo
Abstract : Objectives: We assessed severely and persistently depressed patients' interpersonal self‐efficacy, problems, and goals, plus changes in interpersonal functioning and depression during 20 weeks of group therapy. Method: Outpatients (32 female, 26 male, mean age = 45 years) completed interpersonal circumplex measures of goals, efficacy, and problems before completing 20 weeks of manualized group therapy, during which we regularly assessed depression and interpersonal style. Results: Compared to normative samples, patients lacked interpersonal agency, including less self‐efficacy for expressive/assertive actions; stronger motives to avoid conflict, scorn, and humiliation; and more problems with being too submissive, inhibited, and accommodating. Behavioral Activation and especially Cognitive Behavioral Analysis System of Psychotherapy interventions produced improvements in depression and interpersonal agency, with increases in "agentic and communal" efficacy predicting subsequent decreases in depression. Conclusions: While severely and persistently depressed patients were prone to express maladaptive interpersonal dispositions, over the course of group therapy, they showed increasingly agentic and beneficial patterns of cognitions, motives, and behaviors.